FOOD AND FEEDING HABITS OF CHANNA PUNCTATUS (BLOCH, 1973) FROM WATER BODIES OF NADIA DISTRICT, WEST BENGAL - CHAKRABORTY, RUPALI; DAS, SUDHIR KUMAR; BHAKTA, DIBAKAR (Journal of the Inland Fisheries Society of India, 2021)
Food and feeding habits of Channa punctatus (Bloch, 1793) was investigated from the water bodies of Nadia district, West Bengal during October 2003 to May 2004. A total 348 specimen were examined in two groups viz., group I (less than 110 mm) and group II (more than 110 mm) for convenience of discussion. The average RLG value for the group I was 0.65 and group II as 0.75. The average GaSI value was 3.77 during October and 3.62 during November when sexes could not be identified due to rudimentary stages of the gonads. The highest value of GaSI for male was recorded during February (3.24) and lowest during May (2.28) and for females the value was 3.27 during February and 2.06 during May. There was significant variation (P<0.05) in GaSI values during the period of study. The food items observed in the guts were insects, fishes, crustacean, molluscs, worms, animal matter, decayed organic matter, algae, plant matter, sand, mud and miscellaneous items. Fish was the principal food item, followed by insects and crustaceans. Key words: Food and feeding habits, Channa punctatus, gastro-somatic index